Product Differentiation and Commonality in Design: Balancing Revenue and Cost Drivers - Desai, Preyas; Kekre, Sunder; Radhakrishnan, Suresh; Srinivasan, Kannan (Management Science, 2001)
Product design decisions substantially affect the cost and revenue drivers. A design configuration with commonality can lower manufacturing cost. However, such a design may hinder the ability to extract price premiums through product differentiation. We explicitly investigate the marketing-manufacturing trade-off and derive analytical implications for three possible design configurations: unique, premium-common, and basic-common. Our model considers two distinct segments of consumers. Some of the implications of our analysis are not readily apparent. For example, when the high-quality component is made common, the average quality of the products offered to the two segments increases. One may infer that with higher average quality, higher prices or higher total revenues might ensue. However, this may not be the case, as detailed in the paper. Finally, our analysis provides a useful framework to develop an index that can rank order components in terms of their attractiveness for commonality.